The Economics of the Carbon in Pulp Treatment of Low Grade Flotation Tailings: A Pilot Study - R. H. O. Wagner (Canadian Institute of Mining, Metallurgy and Petroleum, 1984)
"This paper describes the bench testing, pilot plant studies of alternative flowsheets, to determine the feasibility of gold recovery, by carbon in pulp extraction, in the Schumacher Mill gold flotation tailings. The economics were calculated based on pilot plant recoveries and actual industry operating costs.The economics of the carbon in pulp treatment of the gold flotation tailings were not justifiable. The economics of desliming the gold flotation tailings followed by carbon in pulp treatment were marginal, but favourable. INTRODUCTIONPamour Porcupine Mines, Limited is a gold, silver and copper producer located in Timmins, Ontario. In 1983 the head grade of Pamour's gold ores averaged nine one hundredths of a troy ounce of gold per short ton.Pamour operates two area mills to concentrate the gold ores. Free milling gold ores are processed at the Pamour One Mine mill, whereas the refractory carbonaceous gold ores, and complex gold, silver, and copper sulphide ores, are processed through the Schumacher Mine mill.The complex Schumacher mill feed ores do not all react favourably to flotation methods, consequently this study was commissioned to investigate the feasibility of the carbon in pulp cyanidation of the Schumacher mill gold flotation tailings. These tailings contain ten to fifteen percent of the gold in the mill feed. During the study period, the average grade of the Schumacher mill flotation tailings was nine one thousandths of a troy ounce of gold per ton, or one quarter of a gram of gold per metric tonne."